RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN UBI KAYU VARIETAS ADIRA 1 DAN ADIRA 4 TERHADAP PUPUK ORGANIK HAYATI VAM MIKORHYZA - Ferdinandus Ronsumbre; Yosefina Mangera; Ni luh Sri Suryaningsih (Musamus University, 2019)
The research of response of growth and production of cassava plants of variety Adira 1 and Adira 4 towards Vam Mikorhyza fertilizer is conducted to figure out the response of plants towards fertilizer given so that the plants can reach good growth and production. This research used the random design of the factorial group, which consists of 2 factors. The first factor was the variety, consists of 2 variety they were variety Adira 1 (V1) and variety Adira 4 (V2) and the second factor was fertilizer, consists of 2 fertilizer they were Vam Mikorhyza (P1) and compost (P2). Each factor was combined into four treatment combinations which consist of treatment V1P1, V1P2, V2P1, and V2P2. The four treatment combinations were repeated 3 times so it was obtained 12 partition units of the experiment, which was analyzed by analysis of variance. The highest weight of tubers production obtain from Adira 4 variety (V2) was the production reach 28,833 ton ha-1, while the lowest one obtain from Adira 1 variety (V1) with average produced of tubers only 24,683 ton ha-1.